A straightforward synthesis of phenyl boronic acid (PBA) containing BODIPY dyes: new functional and modular fluorescent tools for the tethering of the glycan domain of antibodies. Issue 53 (30th September 2019) - Giacomazzo, Gina Elena; Palladino, Pasquale; Gellini, Cristina; Salerno, Gianluca; Baldoneschi, Veronica; Feis, Alessandro; Scarano, Simona; Minunni, Maria; Richichi, Barbara
Abstract : PBA-BODIPY dyes as functional and modular fluorescent probes for the tethering of the glycan domain of mAbs. Abstract : We report here on the efficient and straightforward synthesis of a series of modular and functional PBA-BODIPY dyes 1–4 . They are an outstanding example of the efficient merge of the versatility of the 3, 5-dichloro-BODIPY derivatives and the receptor-like ability of the PBA moiety. The potential bioanalytical applicability of these tools was assessed by measuring the binding to glycan chains of antibodies by a Quartz Crystal Microbalance (QCM).